VD_FINDINFO HC / 2019 / 951 vom 29. Oktober 2019 - VD Tribunal cantonal (2019)
MESURE PROVISIONNELLE, ACTION EN DIVORCE, MODIFICATION DES CIRCONSTANCES, ACTION EN MODIFICATION, IMPORTANCE NOTABLE | 179 CC